Lemongrass essential oil nanoemulsion formulations based on tragacanth gum and guar gum as durable anti-mosquito fabric finishing agents - Abdullah, Nurul Nabila Aini; Kamari, Azlan; Wong, Siew Tin Susana; Yusof, Norjan; Othman, Hidayatulfathi; Hussein, Mohd Zobir; Hargreaves, Justin S. J. (Springer Science and Business Media Deutschland, 2024)
Mosquito-repellent textiles are classified as protective textiles designed to mitigate the presence of mosquito species recognised as vectors for diseases such as malaria and dengue fever. This study aimed to explore the feasibility of employing a nanoemulsion system containing lemongrass essential oil encapsulated with biopolymers, specifically tragacanth gum and cationic guar gum, as finishing materials on cotton and polyester fabrics. Being anionic biopolymer, tragacanth gum has resulted in outstanding zeta potential, polydispersity index, particle size and encapsulation efficiency with the values of − 38.1 mV, 0.2, 14.1 nm and 99%, respectively. The positively charged guar gum that interacted with aluminium chloride led to precipitation, which disfavoured retention and repellency properties. Based on correlation coefficient (R2) values for tragacanth gum (0.9832) and cationic guar gum (0.9761)-based nanoemulsions, the release of lemongrass essential oil from nanoemulsions followed the Korsmeyer–Peppas kinetic model. Following five cycles of washing and heating, the retention of tragacanth gum-based nanoemulsion on cotton and polyester was determined as 62% and 46%, respectively. From an Excito chamber study, 64% of Aedes aegypti were successfully repelled from nanoemulsion-treated cotton, whereas 53% of the same mosquito species were repelled from nanoemulsion-treated polyester. Overall, results from this study are in line with the mosquito vector control initiative outlined by the World Health Organization.